Automation of Process Planning and Robot Motion Planning in Assembly Operations Considering Component Interference - Miyaji Daiki; Nakatsuji Hidenori; Nishida Isamu (International journal of automation technology, 2025)
Currently, the demand for high-mix, low-volume production is increasing in many manufacturing facilities, and hence, there is a growing demand to reduce the lead time for process planning. Traditionally, process planning for assembly operations is heavily reliant on the knowledge and experience of operators. However, due to the aging population and the declining number of young adults entering the manufacturing industry, labor shortages have become a major issue, which increases the demand for automated assembly process planning systems. To address this issue, this study proposes a system that automatically determines the assembly sequence and robot motion path. Each component of the computer-aided design model in standard triangulated language format consisting of multiple parts was moved along each axis, and the interference with other components was evaluated to derive the connectivity relationships between the parts. By hierarchically structuring the components, the assembly sequence was determined. In addition, by computing the discrete movement positions of the assembly parts and considering interference with the product model, the robot motion path was computed and the motion program was generated automatically. A case study was conducted to validate the proposed system. In the case study, the generated motion program was used to compute the robot’s posture by applying inverse kinematics. In addition, assembly simulations were carried out and the results confirmed that the assembly operation could be executed. Furthermore, experiments were conducted using an industrial robot, and the results demonstrated that the assembly operations could be performed automatically without any interference between the parts.